Identification of miRNA in Sheep Intramuscular Fat and the Role of miR-193a-5p in Proliferation and Differentiation of 3T3-L1 - Han, Fuhui; Zhou, Lisheng; Zhao, Le; Wang, Lei; Liu, Lirong; Li, Haijuan; Qiu, Jixian; He, Jianning; Liu, Nan (Frontiers in Genetics, 2021)
Intramuscular fat (IMF) is one of the most critical parameters affecting meat quality. Muscle content is mainly affected by genetic factors. MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression that degrade their RNA targets or inhibit the translation of messenger RNAs (mRNAs). However, research on the molecular mechanisms involved, particularly the role of microRNAs, in the development of sheep IMF deposition is still lacking. We used RNA sequencing to explore the role of miRNA in IMF deposition. To do that, we identified expressed miRNAs in longissimus thoracis et lumborum (LTL) samples of 2-month-old (Mth-2) and 12-months-old (Mth-12) Aohan fine-wool sheep (AFWS). We found 59 differentially expressed miRNAs (DE-miRNA) between these age groups and predicted their 1,796 target genes. KEGG functional enrichment analysis revealed eight pathways involved in lipid metabolism-related processes, including fatty acid elongation and the AMPK signaling pathway. A highly expressed DE-miRNA, miR-193a-5p, was found to serve a function in 3T3-L1 preadipocyte differentiation. Luciferase assay demonstrated that miR-193a-5p directly binds to the 3’-UTR region of ACAA2. Further functional assays proved that overexpression of miR-193a-5p inhibited 3T3-L1 preadipocyte proliferation, as evidenced by decreased mRNA and protein expression of CDK4 and Cyclin B. CCK-8 assay showed that miR-193a-5p significantly inhibited cell proliferation. Similarly, the overexpression of miR-193a-5p inhibited 3T3-L1 preadipocyte differentiation and adipocyte-specific molecular markers’ expression, leading to a decrease in PPARγ and C/EBPα. Inhibition of miR-193a-5p had the opposite effects. Our study lists the miRNAs associated with intramuscular lipid deposition in sheep and their potential targets, striving to improve sheep meat quality.